Responsibility in the School Context - Development and Validation of a Heuristic Framework - Helker, Kerstin; Wosnitza, Marold (Frontline Learning Research, 2014)
Existing research has identified feelings of responsibility as having major motivational implications for a person’s actions. A person identifying as being responsible for a certain task will perceive themselves as self-determined and thus invest considerable effort in the task. Despite being coneptualised as an individual’s sense of internal obligation, responsibility in everyday contexts is often attributed by and to other people. Different perspectives on responsibility may, however, not always overlap, especially in the school context where tasks and liabilities often remain ill-defined. This paper thus presents a framework of responsibility in the school context which assumes teachers, students and parents to share a certain number of microsystems which may (indirectly) influence one another. In order to test the usefulness of the proposed framework, a series of studies were conducted collecting data on teachers’, students’ and parents’ views of their own and one another’s responsibility in the school context. 4339 statements were assigned to categories representing different parts of the framework and reveal its usefulness for describing the complexity of responsibility attributions and its influences in the school context. Findings show the framework will be helpful to embrace existing research and develop questions for further research that address central educational issues such as student and teacher motivation, teacher burnout as well as prerequisites for students’ high or low achievement.